IDENTIFIKASI TINGKAT KECEMASAN PENDERITA HIPERTENSI PADA MASA PANDEMI COVID 19 DI PUSKESMAS MATARAM - Dian Istiana; Dewi Nur Sukma Purqoti; Ni Putu Eka Mustikawati (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2021)
Silent killer is the nickname of hypertension because someone who has hypertension has even been for years often not aware until complications occur. Hypertension is one of the cormorbid in covid 19 cases so that anxiety is experienced by people with hypertension during the covid 19 pandemic. This study aims to identify the extent of anxiety experienced by people with hypertension. The study used descriptive methods with a crosssectional approach. The results of the study were obtained from 87 respondents in this study that the most respondents were in the age group of >61 years as many as 77 people (88.5%), Female sex as many as 52 people (59.8%) Most respondents worked as retirees as many as 63 people (72.4%) and had a moderate anxiety level of 35 people (40.2%).The conclusion is that there are still many people with hypertension who experience anxiety so that the role of nurses is needed in improving education related to the handling of hypertension in the pandemic covid19 era.